Improving Independent Logic Skills through Spatial Illustration Intervention in Children with Autism Spectrum Phase A Level at SLB, Deliserdang North Sumatera - Yeanny Suryadi; Hastratuddin Siregar (International Journal of Multidisciplinary Sciences and Arts, 2025)
This study aims to analyze the effect of an intervention using spatial illustration media in the form of room illustrations with objects inside them on improving the independence skills of children with special needs (CwSN) with autism spectrum disorder at the elementary level (Phase A) of a Special School in Deliserdang, North Sumatra, Indonesia. The study was conducted at a Special School using a mixed-methods approach involving 13 children as subjects, regardless of gender or age. The intervention was carried out over three weeks, with 60 minutes of intervention per week, through activities matching objects with their corresponding rooms. Quantitative data were analyzed using simple linear regression, showing that students’ independence scores increased by an average of 1.192 points each week. Interview data collected from parents supported these findings, indicating that the skills practiced in class began to be applied in daily life at home, such as placing shoes on the rack or taking books independently. Thus, it can be concluded that routine interventions using spatial illustration media have a positive effect on the independence skills of children with autism spectrum disorder, particularly at the elementary level of Special Schools.